2019
DOI: 10.3389/fimmu.2019.01095
|View full text |Cite
|
Sign up to set email alerts
|

Severe Fever With Thrombocytopenia Syndrome Virus-Induced Macrophage Differentiation Is Regulated by miR-146

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging hemorrhagic fever with a high mortality rate in humans, which is caused by SFTS virus (SFTSV), a novel phlebovirus in the Bunyaviridae family, is tick borne and endemic in Eastern Asia. Previous study found that SFTSV can infect and replicate in macrophages in vivo and in vitro . However, the role of macrophages in virus replication and the potential pathogenic mechanisms of SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…These observations indicate that this miRNA is gaining novel targets and losing existing targets relatively rapidly, with neutral or potentially faster than neutral rates. Notably, miR-146 contributes to diverse immune system functions, including fever response, tumor suppression, T-cell homeostasis, and cytokine production in multiple immune cell lineages [71][72][73][74][75]. It is conceivable that miR-146 targets may be rapidly co-evolving with pathogens as part of an 'arms race' scenario that has frequently been seen in host-pathogen interactions [76].…”
Section: Patterns Of Target Site Loss and Gain For Individual Mirnasmentioning
confidence: 99%
“…These observations indicate that this miRNA is gaining novel targets and losing existing targets relatively rapidly, with neutral or potentially faster than neutral rates. Notably, miR-146 contributes to diverse immune system functions, including fever response, tumor suppression, T-cell homeostasis, and cytokine production in multiple immune cell lineages [71][72][73][74][75]. It is conceivable that miR-146 targets may be rapidly co-evolving with pathogens as part of an 'arms race' scenario that has frequently been seen in host-pathogen interactions [76].…”
Section: Patterns Of Target Site Loss and Gain For Individual Mirnasmentioning
confidence: 99%
“…Cardiac macrophages participate in homeostatic maintenance and tissue repair by producing reparative inflammatory mediators or undergoing polarization (Shiraishi et al, 2016;Ferraro et al, 2019). Some pioneering studies have reported that miR-146b regulates macrophage paracrine signaling and activation under various inflammatory environments (He et al, 2016;Peng et al, 2016;Deng et al, 2019;Zhang et al, 2019); however, little is known about the effects of miR-146b on cardiac macrophages. In the present study, the four most abundant cytokines in wounds (IL-1β, IL-6, TNF-α, and MCP-1) (Mescher, 2017) were found to be significantly reduced in the presence of a miR-146b-5p mimic, whereas many were significantly increased by treatment with an miR-146b-5p inhibitor.…”
Section: Research Articlementioning
confidence: 99%
“…Moreover, whereas the infection of SFTSV possessing wild-type NSs was lethal in IFNAR −/− mice, recombinant SFTSV possessing NSs-P 102 A rescued 70% of mice, suggesting IL-10 expression might be a key factor that contributes to the pathogenesis of SFTSV [47]. Interestingly, other reports demonstrated that SFTSV or SFTSV NSs induces the expression of micro-RNA (miRNA)-146b, which is known to mediate macrophage differentiation by upregulation of IL-10, resulting in THP-1 monocytes skewing towards an anti-inflammatory M2 phenotype [48]. The upregulation of IL-10 and generation of an M2 phenotype may indeed be beneficial in the context of a viral infection in order to establish persistence as has been described for other viruses [126].…”
Section: Pro-inflammatory Activation and Suppression By Banyangvirus Nssmentioning
confidence: 99%
“…The cellular receptor for SFTSV and HRTV has been identified as dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN), which is expressed on macrophages and dendritic cells, implying that these cells are the primary cellular target for viral replication [44,45]. Indeed, in vitro studies have demonstrated the ability of immortalized human and mouse macrophage cell lines to support replication of SFTSV [46][47][48]. Moreover, other C-type lectins such as DC-SIGN related (DC-SIGNR) and liver and lymph node sinusoidal endothelial cell C-type lectin (LSECtin), when expressed on non-permissive cells, can support viral entry [49].…”
Section: Target Tissues/cells and Cellular Receptorsmentioning
confidence: 99%